Meteorological data from Svartberget, Hygget AWS - Svartberget Research Station (Swedish University of Agricultural Sciences, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Svartberget Research Station (2025). Meteorological data from Svartberget, Hygget AWS, 2016–2018 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/rF42Tlo548BYOAQn2lUOkcE4
Keywords: Svartberget Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Soil temperature; Soil temperature; Cumulative shortwave radiation; Cumulative shortwave radiation; Vapour pressure; Vapour pressure; Wind speed; Wind speed; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap